Human impacts mediate freshwater invertebrate community responses to and recovery from drought - Sarremejane, Romain; England, Judy; Dunbar, Mike; Brown, Rosalind; Naura, Marc; Stubbington, Rachel (Wiley, 2024)
Drought is an increasing risk to the biodiversity within rivers—ecosystems which are already impacted by human activities. However, the long‐term spatially replicated studies needed to generate understanding of how anthropogenic stressors alter ecological responses to drought are lacking. We studied aquatic invertebrate communities in 2500 samples collected from 179 sites on rivers emerging from England's chalk aquifer over three decades. We tested two sets of alternative hypotheses describing responses to and recovery from drought in interaction with human impacts affecting water quality, fine sediment, water temperature, channel morphology, flow and temporal change in land use. We summarized communities using taxa richness, an index indicating tolerance of anthropogenic degradation (average score per taxon, ASPT) and deviation from the average composition. Responses to drought were altered by interactions with human impacts. Poor water quality exacerbated drought‐driven reductions in taxa richness. Drought‐driven deviations from the average community composition were reduced and enhanced at sites impacted by flow augmentation (e.g. effluent releases) and flow reduction (e.g. abstraction), respectively. Human impacts altered post‐drought recovery. Increases in richness were lower at sites impacted by water abstraction and higher at sites with augmented flows, in particular as recovery trajectories extended beyond 3 years. ASPT recovered faster at sites that gained woodland compared to urban land, due to their greater recovery potential, that is, their lower drought‐driven minimum values and higher post‐drought maximum values. Synthesis and applications. We show that communities in river ecosystems exposed to human impacts—in particular poor water quality, altered flow volumes and land use change—are particularly vulnerable to drought. These results provide evidence that management actions taken to enhance water quality, regulate abstraction and restore riparian land use could promote ecological resilience to drought in groundwater‐dominated rivers such as globally rare chalk streams and other rivers of the Anthropocene, as they adapt to a future characterized by increasing climatic extremity.
Keywords: abstraction; anthropogenic impact; chalk stream; drought; macroinvertebrate; multiple stressors; resilience; resistance; 41 Environmental Sciences; 31 Biological Sciences; 3103 Ecology; 15 Life on Land; 14 Life Below Water; Ecology; 3109 Zoology; 4104 Environmental management